Work-based learning models in engineering curricula: insight from the French experience. (2nd January 2020) - Rouvrais, Siegfried; Remaud, Bernard; Saveuse, Morgan
ABSTRACT: To favour an early exposure of students to professional practice, several engineering higher education institutions have implemented integrated curricula, as proposed in the international CDIO educational framework. In the 1990s, the French engineering education accreditation body introduced in its quality standards a compulsory internship period. Based on this national experience, this article sets out the various models of internships and apprenticeships in French engineering education and presents two curriculum integrations: one in a highly selective public graduate Grande Ecole  and another in a private multisite engineering institution strongly linked to professional branches and national qualification framework. To provide some inputs and rationales to educational programme designers in other national contexts, this article proposes to extend the CDIO framework to systematically include work-based learning as integrated activities, to better match industry requirements and student competency expectations as future engineers.